Pop - Korman, Gordon. (Balzer + Bray, 2009)
Lonely after a midsummer move to a new town, sixteen-year-old high-school quarterback Marcus Jordan becomes friends with a retired professional linebacker who is great at training him, but whose childish behavior keeps Marcus in hot water.